Peran Satuan Pelayanan Balai Teknik Perkeretaapian (BTP) Kelas II Padang dalam Pengawasan Jalur Kereta Api Non-aktif di Sumatera Barat - Sufinidea Salsa; Iip Permana (Lembaga Yasin AlSys, 2025)
The condition of inactive railway lines in West Sumatra requires continuous monitoring to ensure that infrastructure assets are preserved and remain available for future use. This study aims to analyze the role of the Service Unit of the Class II Padang Railway Engineering Center (Balai Teknik Perkeretaapian, BTP) in monitoring inactive lines and to identify the challenges encountered. A qualitative descriptive approach was employed, with data collected through interviews, observations, and document studies, and data validity tested using source and technique triangulation. The findings reveal that the Class II Padang BTP Service Unit performs monitoring functions through direct inspections and community outreach. However, monitoring implementation faces challenges such as limited budget, infrastructure, accessibility, human resources, and low cooperative response from the community. Despite these constraints, monitoring efforts are carried out optimally to ensure that inactive railway infrastructure remains well maintained. Keywords: Monitoring; Inactive Railway Lines; Service Unit; Railway Engineering Center; West Sumatra